Effect of Group Counseling on the Type of Delivery in Nulliparous Women: A Randomized Controlled Trial - Zinat Jourabchi; Zahra Roshan; Mahmood Alipour; Fatemeh Ranjkesh (Hamadan University of Medical Sciences, 2018)
Background: Pregnancy and childbirth is one of the most important stages in women's lives. One of the reasons for women's desire to choose interest in cesarean delivery is lack of enough knowledge in choosing their birth method. This research studies the effect of group counseling on the type of delivery in Nulliparous women. Methods: This is a controlled randomized trial will be conducted in 160 pregnant nulliparous women referred to Health Center from 95- 96 in Hamedan. The inclusion criteria were as follows: Women with gestational age 20-23 weeks. The exclusion criteria were as follows: maternal medical and Psychological diseases. The samples were randomly allocated to group intervention (n=80) and control groups (n=80). In both groups, mothers received routine prenatal care. The intervention group additionally received 8 sessions weekly group counseling. Data was collected by a checklist consisting of demographic, pregnancy, and delivery information and was analyzed by statistical testes such as T-test and chi squares. P<0.05 was considered as significant. Result: A significant difference was also observed between two groups in the rate of normal vaginal delivery (P=0.04). The results indicated that the group counseling significantly increased the physiologic delivery (53.2%) in the intervention group compared by the control group (22/2%) (P=0/002). Conclusion: The results of the study showed that the presence of nulliparous women in the group counseling increases the rate of physiologic delivery and is suggested as one of the methods of implementing pregnant women's care program.